2019
DOI: 10.21873/anticanres.13338
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Access Potentially Endangers Esophageal Carcinoma Patients Under Multi-modality Therapy: A Population-based Study

Abstract: Background/Aim: This study aimed to evaluate the clinical outcome of esophageal cancer (EC) patients with enteral access (EA) undergoing multimodality therapy. Patients and Methods: This retrospective study analyzed data between 1997 and 2012 in Taiwan using the National Health Insurance Research Database. Patients with newly-diagnosed EC undergoing multimodality therapy were identified and classified as either EA group or no-EA group. Results: The mortality incidence of EC patients with EA was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A retrospective cohort study in patients with EC, under multimodal therapy in conjunction with EN, concluded that there is a potential increase in the risk of mortality with this type of nutrition 9 . Regarding the quality of life of patients undergoing chemoradiotherapy in relation to EN, Yu et al, 10 compared NGT, esophageal stent and ostomies with feeding tubes, concluding that there is slightly worse quality of life in patients with esophageal squamous cell carcinoma using NGT, compared with the percutaneous route during chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study in patients with EC, under multimodal therapy in conjunction with EN, concluded that there is a potential increase in the risk of mortality with this type of nutrition 9 . Regarding the quality of life of patients undergoing chemoradiotherapy in relation to EN, Yu et al, 10 compared NGT, esophageal stent and ostomies with feeding tubes, concluding that there is slightly worse quality of life in patients with esophageal squamous cell carcinoma using NGT, compared with the percutaneous route during chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%